IMPLEMENTASI PEMBELAJARAN TAFSIR ALQURAN PADA FAKULTAS AGAMA ISLAM UNIVERSITAS DHARMAWANGSA MEDAN - M. Ridwan Hisda (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2017)
ABSTRACT: The object of this research is that some people Lecturer, Dean and Vice Dean of the Facultyof Islamic Studies University Dharmawangsa, Rector and Vice-Rector, Head of the Education FoundationDharmawangsa, some students of Faculty of Islamic Studies University Dharmawangsa, Secretary of theFoundation, Treasurer Education Foundation Dharmawangsa that can provide information to The importanceof this study. By using Snowball Sampling technique, that is by selecting several people ofresearch object in chains, after the data is considered saturated / enough, the number of research subjectis stopped. Data collection in this study, using the system of interviews and observation, as well as studydocuments (library research).The results showed that learning implementation interpretation of theKoran on Faultas Islamic University Dharmawangsa Medan, run smoothly for both the learning objectiveinterpretation of the Koran, lesson planning, teaching methodology, syllabus, lectures and evaluationsystem is applied, is in conformity with the Standard Operational Procedures (SOP), which Shall beguided by Law no. 55 of 2007 on religious and religious education, explained that religious educationaims to live, and practice religious values that harmonize their mastery in science, technology and art.To the students of Faculty of Islamic Studies University Dharmawangsa Medan, is equipped with theknowledge of the Koran, such as the science of interpretation of the Koran, which is how to understand themeaning of interpretation of the Koran, the method learning methods interpretation of the Koran, sciencethe other sciences in order to study interpretation of the Koran, such as science balaghah, science tools,qawa’id, and morals of the Qur’an, while the learning function interpretation of the Koran, so students donot get stuck on the error - error in the understanding of the Koran, what its practices.This study aims todetermine how the implementation of the Koran Interpretation Learning the Faculty of Islamic StudiesUniversity Dharmawangsa Medan, what is the purpose of learning the Koran Tafsir, how prencanaanya,whether it is in accordance with the Decree of the Directorate of High No. 43 / DIKTI / Kep. / 2006, onIslamic Religious Education in Lembga - formal institutions starting from elementary, junior high, highschool, and college level. How syllabus perkuliahnnya, systems and methods are used, how the evaluationsystems are applied, as well as the factors - factors that support and hinder the implementation ofQur’anic Tafsir learning at Faculty of Islamic Studies University Dharmawangsa Medan.